مفهوم الإنسان عند طه عبد الرحمن وإسهاماته في تجديد علم الكلام - عتيبي، سوسن مزيد (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2018)
The research is conducted to illustrate the concept of man by Taha Abdulrahman as one of the most central concepts of his philosophy. The researcher divided the concept of man according to Taha Abdulrahman's studies to him, human beings fall under the category of the moral man, prodigy man and honest man. After constructing the concept of man, the researcher tested it on Islamic theology in order to evaluate Taha Abdulrahman's analysis. The structural approach to build the concept of man, the inductive approach to collect the meaning of man, the analytical approach to analyse Taha Abdulrahman's sources, critical approach and comparative approach to compare between Taha Abdulrahman and some scholers thoughts such as Ibn Timayah was applied in this research. The thesis concluded with a number of results. The most important one is the value of the concept of man, which is key in understanding Taha Abdulrahman's philosophy and the impact of the concepts on Islamic and human science studies.